An Insight into Synthesis, Optical Properties, and Applications of Green Fluorescent Carbon Dots - Sanjeev Kumar; Jyoti Gaur; Sandeep Kaushal; Jasvir Dalal; Mrinmoy Misra; Harpreet Kaur; Supreet Kaur; Navneet Kaur; Gautam Singh; Gurjinder Singh (Crystals)
In the ever-advancing field of nanotechnology and nanoscience, luminescent carbon dots, or carbon quantum dots, have emerged as one of the most up-and-coming carbon-based nanomaterials in recent years due to their diverse physicochemical properties, which include low toxicity, ease of synthesis, superior photostability, excellent water solubility, high specific surface areas with ease of surface functionalization, and unique electronic and optical properties. They exhibit two-photon absorption and unique tunable fluorescence emission across a wide range of wavelengths, which can be precisely controlled by surface modifications and particle size. These characteristics have led to their widespread usage in a variety of applications, including optical/fluorescent sensing, electrochemical sensing, and energy-related fields, such as light-emitting diodes, photovoltaic supercapacitors, bioimaging, drug delivery, and antimicrobial research. Recently, focus has shifted to the green synthesis of carbon dots, with significant success achieved in this area, opening a plethora of opportunities in both basic and applied sciences. This review is a comprehensive study of milestones achieved in the area of green carbon dots. This review starts with the historical background of luminescent materials and how carbon dots/carbon quantum dots have been emerging as the stars among all luminescent nanomaterials. The challenges of conventional synthesis methods for nanoparticles are also discussed, with a detailed review of the various green synthesis processes reported to date. This section provides insights into widely accepted formation mechanisms and their influence on the shapes and sizes of CDs. In the next section, various physical properties of CDs are discussed, highlighting characteristics such as high quantum yield, photoluminescence stability, and chemical inertness, which make them exceptional nanomaterials. Last but not least, various CD-related challenges and future prospects are highlighted. Overall, this review provides details of recent developments in the area of green CDs.